Real color volume model of cadaver for learning cardiac computed tomographs and echocardiographs. - Chung, Beom Sun; Chung, Min Suk (Surgical & Radiologic Anatomy, 2021)
Purpose: It is difficult for medical students and novice clinicians to interpret cardiac computed tomographs and echocardiographs. This study was intended to help familiarize them with the clinical images of the heart by providing software to browse the various planes of a heart's volume model with real color and high resolution. Methods: On the sectioned images of a male cadaver, the heart and adjacent structures were segmented to obtain color-filled images. Volume models of the sectioned images and color-filled images were reconstructed and sectioned to obtain three orthogonal planes and five standard oblique planes. The planes were inputted into lab-made browsing software, which was then distributed free of charge. Results: Users of the software would hopefully progress as follows. After experiencing the real color and high resolution, they would become familiar with the grayscale and low resolution. After experiencing the automatic annotation of the basic heart structures, they would become familiar with the detailed structures. After experiencing the designated planes, they would become familiar with the arbitrary planes. After experiencing the still heart, they would become familiar with the moving heart during echocardiography. Conclusion: The software, with a user-friendly interface and realistic features, is expected to properly orient medical novices to cardiac computed tomography and echocardiography images.